Size matters: Physiological sensitivity of the scallop Argopecten purpuratus to seasonal cooling and deoxygenation upwelling-driven events - Ramajo, Laura; Sola-Hidalgo, Camila; Valladares, María; Astudillo, Orlando; Inostroza, Jorge (Frontiers in Marine Science, 2022)
Environment imposes physiological constraints which are life-stage specific as growth-maintenance and/or growth-reproduction energetic requirements are size and volume-dependent. The scallop Argopecten purpuratus, one of the most important bivalve species subjected to fishery and aquaculture along the Humboldt Current System, inhabits spaces affected by continuous changes in temperature, pH, oxygen, and food availability driven by remote and local oceanographic processes. Specifically, in Chile, this species is mainly cultured in central-north Chile where is permanently affected by upwelling events of dissimilar intensity and duration which generate local conditions of acidification, deoxygenation, and cooling with different magnitudes. However, to date, it remains unknown how this economic valuable resource is physiologically affected throughout its life cycle by the continuous environmental changes driven by upwelling events of different intensities and duration along the year. Here, for the first time, A. purpuratus life-stage physiological sensitivity was assessed at a seasonal scale through a year-field experiment where growth, calcification, and survivorship were evaluated. Our study shows how seasonal differences in the upwelling phenology (here measured as changes in temperature, dissolved oxygen, pH, and primary productivity, but also as the number, duration, and intensity of cooling and de-oxygenation events) notably impacted the A. purpuratus physiological performance from juvenile to adult life-stages. This was especially noticeable during the spring season which showed the most intense cooling and deoxygenation events driven by stronger favorable-upwelling winds and the lowest growth and gross calcification rates (the highest decalcification rates) where adult stages showed the lowest performance. On the other hand, A. purpuratus survivorship was not significantly affected by upwelling intensity which would be providing evidence of the high physiological flexibility and well-locally adapted is this species to fluctuating and occasional stressful environmental conditions. Our results are significantly relevant in the climate change context as some upwelling systems are at risk to change shortly (i.e., an upwelling intensification in frequency and intensity) as a consequence of changes in the atmospheric pressures that modulate favourable-upwelling winds. These changes may certainly increase the climate related-risks of the entire socio-ecological systems related to the fishery and aquaculture of A. purpuratus along the Humboldt Current System.